Phytochemical Analysis and In Vitro Anticancer Activity of Chloroform Extract of Centella Asiatica Leaves Using Lung Cancer (A549) - Sinduja S, Sinduja S; Thomas, Asi; Poornashri, Poornashri; Raghu, Susil; Christinal, Christinal (Journal of Neonatal Surgery, 2025)
Medicinal plants are a cornerstone of traditional medicine and are extensively studied for their therapeutic properties. Among them, Centella asiatica is well known for its diverse pharmacological benefits, including its potential anticancer properties. This study aims to evaluate the phytochemical composition and in vitro anticancer activity of chloroform extract derived from the leaves of C. asiatica against the lung cancer cell line A549. The phytochemical screening revealed the presence of key bioactive compounds such as alkaloids, flavonoids, glycosides, carbohydrates, and amino acids, which are known for their biological and therapeutic effects. The anticancer potential of the chloroform extract was assessed using the MTT assay, which measures cellular viability by evaluating mitochondrial activity. The extract demonstrated significant dose-dependent cytotoxicity against the A549 cell line, with IC50 values indicating its potency. The results highlight the potential of C. asiatica to inhibit cancer cell proliferation and induce cytotoxicity, making it a promising candidate for further development as a natural anticancer agent. Phytochemicals such as flavonoids and alkaloids, which were detected in the extract, have been extensively reported in the literature for their roles in inducing apoptosis, preventing metastasis, and exhibiting antioxidant activity. These properties likely contribute to the extract's anticancer effects observed in this study. Additionally, the presence of glycosides and amino acids may support complementary mechanisms in targeting cancer cells. The findings of this study underscore the potential of C. asiatica as a natural source for anticancer agents, particularly in the context of lung cancer. Future studies should focus on isolating and characterizing specific active compounds, determining their precise mechanisms of action, and conducting in vivo experiments to validate their efficacy. This research also emphasizes the importance of medicinal plants as a sustainable and accessible resource for drug discovery, offering an alternative to synthetic drugs, which often have significant side effects